2013
DOI: 10.1371/journal.pbio.1001692
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Trade-offs Restrict the Evolution of Resistance to Amphotericin B

Abstract: The rarity of clinical drug resistance to the antifungal amphotericin B is explained by the extreme costs that resistance mutations impose upon stress responses and virulence factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
257
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(276 citation statements)
references
References 60 publications
11
257
1
7
Order By: Relevance
“…In fact, in a systematic investigation to define genes whose inactivation confers AmB resistance, it was found that the MIC for AmB against C. albicans was increased more than 3-fold by the deletion of ERG2 or ERG6 or of ERG3 and ERG11 together, all of which are involved in the ergosterol biosynthetic pathway (55). Vincent et al have also reported that the evolution of ERG2/erg2⌬ heterozygotes of AmB-R C. albicans strains requires the presence of Hog1 or calcineurin or high levels of the Hsp90 molecular chaperone (55). However, the changes made in the AmB-R phenotype by the deletion of the ERG genes involve substantial fitness costs because the resistant strains exhibited drastically reduced tolerance not only of oxidative stresses but also of other external stresses such as high temperatures, killing by neutrophils, impairment in the filamentation process, and tissue invasion (55).…”
Section: The Development Of Amb Resistance In Eukaryotic Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in a systematic investigation to define genes whose inactivation confers AmB resistance, it was found that the MIC for AmB against C. albicans was increased more than 3-fold by the deletion of ERG2 or ERG6 or of ERG3 and ERG11 together, all of which are involved in the ergosterol biosynthetic pathway (55). Vincent et al have also reported that the evolution of ERG2/erg2⌬ heterozygotes of AmB-R C. albicans strains requires the presence of Hog1 or calcineurin or high levels of the Hsp90 molecular chaperone (55). However, the changes made in the AmB-R phenotype by the deletion of the ERG genes involve substantial fitness costs because the resistant strains exhibited drastically reduced tolerance not only of oxidative stresses but also of other external stresses such as high temperatures, killing by neutrophils, impairment in the filamentation process, and tissue invasion (55).…”
Section: The Development Of Amb Resistance In Eukaryotic Pathogensmentioning
confidence: 99%
“…Vincent et al have also reported that the evolution of ERG2/erg2⌬ heterozygotes of AmB-R C. albicans strains requires the presence of Hog1 or calcineurin or high levels of the Hsp90 molecular chaperone (55). However, the changes made in the AmB-R phenotype by the deletion of the ERG genes involve substantial fitness costs because the resistant strains exhibited drastically reduced tolerance not only of oxidative stresses but also of other external stresses such as high temperatures, killing by neutrophils, impairment in the filamentation process, and tissue invasion (55). Interestingly, Hsp90, by repressing Ras1-PKA signaling, is known to regulate a key temperature-dependent morphogenetic transition from yeast to filamentous growth that is crucial for virulence in fungal cells (56).…”
Section: The Development Of Amb Resistance In Eukaryotic Pathogensmentioning
confidence: 99%
“…This buffering capacity allows it to modulate the manifestation of preexisting and newly acquired genetic variation within heterogeneous populations of cells, and even whole organisms, thereby dramatically expanding the range of phenotypes on which selection can act (1, 2, 5-7). As a dramatic, therapeutically relevant example, we have shown that this HSP90 buffer enables fungal pathogens spanning ∼1 billion years of evolution to evolve and maintain resistance to every major antifungal in general use (8,9). Now we ask whether HSP90 might serve a similar role in buffering the molecular and genetic heterogeneity present in human tumors and whether low-level inhibition might limit the emergence of drug resistance.…”
mentioning
confidence: 99%
“…Fungal pathogens can become resistant by replacing ergosterol with alternative sterols that do not bind polyenes. However, this results in diminished virulence and has not posed a serious clinical problem (Vincent et al, 2013).…”
Section: Recent Insights Into Biological Activities Of Polyene Macrolmentioning
confidence: 99%